Ethnoreligious Diversity and Harmony in Sanggau, West Kalimantan - Ruslan, Ismail; Amri, Faizal; Hasriyanti, Nunik; Haryanto, Joko Tri; Yusriadi, Yusriadi (LPPM IAIN Kudus, 2024)
The long history of Sanggau, West Kalimantan, shows relations between ethnicities and religions. Several major and open conflict events in West Kalimantan did not hit Sanggau. Despite social tensions, the Sanggau community managed to maintain the harmony of the community. This study is intended to look at the recipes Sanggau community in an effort to maintain community harmony for inter-religious and inter-ethnic, and how to resolve conflicts that have arisen since the past until now. This qualitative research was carried out with a sociological approach, and data collection techniques through interviews with various community leaders, observations on relations between residents, and documentation studies on various documents and publications about Sanggau. The data were analyzed by descriptive analysis. The results of this research show that Sanggau has been awake since the early period, the reform period, until today it is relatively able to maintain harmony and prevent open conflicts. It is common for there to be conflicts in the community, but the Sanggau people have managed to resolve conflicts and maintain their harmony. Existing conflicts related to the construction of houses of worship, religious conversions, and marriages involving couples of different religions can be resolved quickly and appropriately so that they do not become open conflicts. The approach to conflict resolution is carried out by religious leaders, ethnic leaders, and local governments by carrying out local wisdom such as the “Ngudas” ritual which builds harmony as a common identity even though they are ethnically and religiously different.